Brahmo Samaj and Dyal Singh Majithia - Madan Gopal (New Delhi : Uppal Pub. House, 1998)
Contributed articles on the life of Dyal Singh Majithia, 1848-1898, educationist and founder of Tribune, English daily newspaper.
Keywords: Majithia, Dyal Singh, -- 1848-1998.; Educators -- India -- Punjab -- Biography; Journalists -- India -- Punjab -- Biography; Philanthropists -- India -- Punjab -- Biography; Punjab (India) -- Biography